(untitled) (Research, Society and Development, 2023)
Colorectal cancer involves the large intestine and rectum and is responsible for high rates of morbidity and mortality in Brazil due to its silent development. Thus, the objective of this study was to outline a clinical epidemiological profile of colorectal cancer in the state of Minas Gerais using data obtained from DATASUS. This is an observational, cross-sectional, population-based study using secondary data provided by the Department of Informatics of the Unified Health System (DATASUS). The study population consisted of all cases of colorectal cancer diagnosed in the state of Minas Gerais from 2013 to 2022. Approximately 31.813 cases diagnosed during this period were analyzed, with a predominance of female patients and a higher incidence in the 60-69 age group. Regarding topography, C18- Malignant neoplasm of the colon was the most affected, accounting for approximately 62% of cases. It was observed that chemotherapy and surgery were the most commonly used treatments. Additionally, there is an estimate that cases will range from 400 to 450 cases in the state in the first half of 2023. Therefore, this study contributed to a more comprehensive understanding of the epidemiological profile of colorectal cancer in Minas Gerais, highlighting areas of concern and providing essential information for the formulation of effective health policies to reduce the impact of this devastating disease on the population.